A gestão educacional e o processo de elaboração do Plano Municipal de Educação (2015-2025) em São Paulo: das notas taquigráficas à análise dos representantes entrevistados - De Morais, Nicole Claro Moreira (Universidade Federal de São Carlos, 2025)
This research aims to identify and analyze the educational management model of the municipality of São Paulo, based on the actions, political decisions, and strategies developed since 2008 for the formulation of the Municipal Education Plan (2015–2025). In the municipality under study, the process of constructing the Municipal Education Plan (MEP) began in 2008 with Ordinance No. 3,169, which established the Organizing Committee for the MEP Construction Process. This process was finalized in 2015 with the approval of the document, following a long trajectory. For this study, the specific objectives defined were: to understand the mechanisms of management and regulation established within national policy and, in particular, within the policy of the municipality of São Paulo from the 1990s onwards, as well as their political and ideological foundations and their implications for education; to analyze the model and mechanisms of management present in the process of elaborating the MEP; and to examine the participation of civil society and its impact on the decisions made during the elaboration of the MEP. The research adopts a qualitative approach, grounded in: bibliographic research, with theoretical references that supported the theoretical and field discussions; documentary research, based on the stenographic notes produced throughout the Plan’s proceedings in 17 public hearings; and field research, consisting of semi-structured interviews with five representatives who participated in the MEP’s elaboration process. The basic categories of analysis employed were: actors involved, types of participation, location of power, and management mechanisms. Data analysis reveals that the model of democratic management was re-signified or distorted throughout the Plan’s proceedings, adopting a neoliberal logic of organization and regulation, in which social participation became increasingly symbolic and constrained. The political decisions and management strategies employed (whether formally or informally) influenced both the drafting of the MEP and the decision-making process at the time. The review of stenographic notes, combined with the testimonies collected through interviews, demonstrated that ideological divergences and power struggles took center stage in debates that should have focused on educational demands. Thus, the findings indicate that, despite certain efforts to democratize the Plan’s formulation process, disputes and the use of power mechanisms during its proceedings not only shaped the drafting of the document but also reinforced the maintenance of neoliberal logic within the education system of the municipality of São Paulo. Therefore, it can be concluded that the management model identified throughout the elaboration of the MEP translated into the re-signification of mechanisms of democratic management, deeply distorted and ultimately undermined by conservative and managerial models, which appropriated democratic concepts and discourses to legitimize their actions in defense of private interests.
Educational management and the process of elaborating the Municipal Education Plan (2015–2025) in São Paulo: from stenographic notes to the analysis of interviewed representatives
Keywords: Plano municipal de educação; Gestão educacional; Política educacional municipal; São Paulo; Municipal education plan; Educational management; CIENCIAS HUMANAS::EDUCACAO; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL::POLITICA EDUCACIONAL; CIENCIAS HUMANAS::EDUCACAO::PLANEJAMENTO E AVALIACAO EDUCACIONAL::PLANEJAMENTO EDUCACIONAL